PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI DAN SIMULASI TERAPI AKUATIK PADA REHABILITASI PENYINTAS STROKE: COMMUNITY EMPOWERMENT IN POST STROKE REHABILITATION WITH AQUATIC THERAPY - Bambang Trisnowiyanto; Isna Andriani (LPPM Universitas Abdurrab, 2025)
Stroke is a disease that attacks blood vessels in the brain that is not contagious, stroke is the third disease after heart disease and cancer that contributes to the highest mortality rate in Indonesia. Post-stroke sufferers can also be called stroke survivors, in stroke survivors there are generally sequelae in the form of functional physical movement barriers which are often referred to as physical disabilities so that stroke survivors experience obstacles to carrying out daily functional activities such as self-care activities, productivity and leisure activities. This program aims to empower the community in achieving an optimal level of independence in carrying out daily life activities to meet basic human needs. In this phase of physical functional rehabilitation of stroke survivors, the empowerment method used is aquatic therapy modality education as a home therapy program. This community empowerment is shown in community groups with mature age, which is more than 25 years old. Lecture and simulation methods were used to provide information and skills to the community about the application of aquatic therapy in the rehabilitation phase of stroke survivors. Evaluation was conducted using a questionnaire. The results of this activity were attended by 73 participants who were members of the study congregation at Mushala Khairan Senden. The results of the pre-test measurement of the level of knowledge about aquatic therapy. The results of the pre-test measurement of the level of knowledge about aquatic therapy for the rehabilitation of stroke survivors showed 68.5% of participants with insufficient knowledge, 24.7% of participants with sufficient knowledge, and 6.8% of participants with good knowledge. Evaluation after the implementation of community service or post-test showed 26% of participants with insufficient knowledge, 35.6% of participants with sufficient knowledge, and 38.4% of participants with good knowledge. In conclusion, community empowerment through lectures and simulations can increase knowledge and skills about aquatic therapy as a modality of home program therapy in the rehabilitation phase of stroke survivors to achieve independence in functional activities in daily life.